2002
DOI: 10.1021/jp021247g
|View full text |Cite
|
Sign up to set email alerts
|

Energy Landscape and Isotropic Tensile Strength of n-Alkane Glasses

Abstract: We report results from a systematic simulational study of the ultimate mechanical strength of n-alkane glasses for carbon numbers n ) 1, 2, 3, 4, 6, 8, 16, 24, and 48. The ultimate isotropic tensile strength was determined by constructing the equation of state of energy landscape for this homologous series. The tensile strength depends nonmonotonically on carbon number, exhibiting a maximum at n ) 3. The mass density at which fracture occurs initially increases with chain length and then reaches a plateau valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 86 publications
2
24
0
Order By: Relevance
“…A similar decrease of τ was observed in simulations of n-alkanes 43 and experimentally it has been found that ultimate tensile strength of certain polymeric systems, such as amorphous polyethylene, decreases with increasing molecular weight. 63 Such a decrease in τ is non-trivial, since one expects longer chains to exhibit more chain "entanglement".…”
Section: Calculation Of τsupporting
confidence: 80%
See 3 more Smart Citations
“…A similar decrease of τ was observed in simulations of n-alkanes 43 and experimentally it has been found that ultimate tensile strength of certain polymeric systems, such as amorphous polyethylene, decreases with increasing molecular weight. 63 Such a decrease in τ is non-trivial, since one expects longer chains to exhibit more chain "entanglement".…”
Section: Calculation Of τsupporting
confidence: 80%
“…Our results are based on molecular dynamics (MD) computer simulations, using non-equilibrium methods to evaluate η, 40,41 and exploit the "inherent structure" formalism to determine τ . 42,43 We find that the rod-like nanoparticles give the largest enhancement to η, which we correlate with the presence of chains that bridge between the nanoparticles. The sheet nanoparticles offer the weakest increase in η, and correspondingly have the smallest fraction of bridging chains.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…3b and 3c, cohesive failure does show qualitatively different structural consequences in ultrathin and thicker films. While ultrathin films fail by forming planar voids between molecular layers parallel to the substrates, thicker films generally fail by forming voids that are 'local' and more isotropic (more balanced in the transverse and normal directions), not so different from the "bubble-like" voids that form from weak spots in bulk materials (Sastry et al, 1997;Shen et al, 2002). Note that this local cohesive failure mechanism produces a film with a much smaller tensile strength than the ultrathin film of Fig.…”
Section: Resultsmentioning
confidence: 94%